PROBLEMS OF IMPLEMENTATION OF THE RIGHT TO A FAVORABLE ENVIRONMENT IN THE REPUBLIC OF KAZAKHSTAN IN THE CONDITIONS OF DIGITALIZATION (Journal of actual problems of jurisprudence, 2024)
The right to a favorable environment is a fairly broad concept; the right of citizens to favorable environmental conditions today is an unshakable social value, the stability of which is directly guaranteed by the Constitution of the Republic of Kazakhstan. The advent of digital technology in the modern era has opened up opportunities to support this right.This scientific study provides a legal assessment of the current national, international and foreign legislative and regulatory framework in this area. The scientific article examines the most pressing issues of implementing the right to a favorable environment in the Republic of Kazakhstan in the context of digitalization, which has been implemented very intensively in recent years. The main goal of this study is a comprehensive and comprehensive study of the implementation of the right to a favorable environment in the Republic of Kazakhstan in the context of digitalization.The research work examines not only legal issues of implementation and protection of the human right to a favorable environment, but also conducts a comparative legal analysis with the legislation of foreign countries. This article complements theoretical knowledge in the field of environmental protection. The authors analyze the use of digital advances in environmental issues and suggest ways to improve legislation in this area.Key words: Environment, favorable environment, protection of rights to a favorable environment.